Knowledge and practice of positioning technique and attachment of breastfeeding among postnatal mothers (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Good positioning technique and attachment of breastfeeding is beneficial for both child and mother. The aim of this study was to identify knowledge and practice of positioning technique and attachment of breastfeeding among postnatal mothers.Methods: A cross-sectional study was carried out among postnatal mothers who were admitted in Patan Hospital, Lalitpur, Nepal. Data were collected by structured interview regarding knowledge and practice of positioning technique and attachment of breastfeeding using WHO Observation. A non-probability, purposive sampling technique was used. Data was analyzed by SPSS.Results: Out of 168 respondents, 14 (8.3%) had inadequate knowledge and 78 (46.4%) had poor practice. Nine (5.4%) had poor technique in sitting position and 16 (9.5%) in lying position. There was statistically significant association between parity and knowledge. Practice was associated with parity and age. Overall knowledge correlated with practice.Conclusions: More than half of postnatal mothers had moderate level of knowledge and good practice. Parity was associated with knowledge and practice.